Electrochemical study on molten iron-carbon electrodes in slag and their decarburization by slag/metal reaction. (20th February 2022) - Judge, W.D.; Paeng, J.; Azimi, G.
Highlights: Carbon greatly increases exchange current and capacitance between molten iron and slag. Apparent standard heterogeneous rate constant for decarburization half-cell determined. During decarburization, surface concentrations of the first and second intermediates are ∼1–4 and ∼10–100 × 10 –10  mol cm –2 . Electrochemical rate constants compared to reaction rates from gas chromatography. Abstract: An electrochemical study on molten iron-carbon electrodes in slag and their decarburization during anodic polarization was performed at 1600 °C to obtain information relevant to steelmaking. Carbon concentration was varied from 4.5 to 0.2 wt% to cover the range of interest between pig iron tapped from blast furnaces and steel tapped from oxygen converters or electric arc furnaces. Impedance spectra were measured at the rest potential and at applied direct current biases, and results were fitted to a faradaic decarburization reaction proceeding through two adsorbed intermediates. At the rest potential, carbon significantly increases faradaic activity at the metal/slag interface as evidenced by a strong increase in exchange current and interfacial capacitance with carbon activity. The apparent standard heterogeneous rate constant of the anodic decarburization half-cell was determined using the dependence of exchange current on carbon activity. During electrochemical decarburization, interfacial capacitance decreases significantly which is consistent with changes in surface concentrations of intermediates. Using a comprehensive kinetic model, surface concentrations of intermediate adsorbed species were determined during anodic polarization in the Tafel region. Results from impedance spectroscopy were compared with those obtained by gas chromatography during constant-current decarburization. Graphical abstract: Image, graphical abstract